Capital theory - Bliss, C. J.; Cohen, Avi Jonathan; Harcourt, Geoffrey Colin (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2005)
This comprehensive three-volume edition brings together the most important contributions in capital theory, from its classical origins to its modern manifestation in endogenous growth models. The readings examine the recurring controversies, and the two incisive, and sharply contrasting introductions by Bliss and by Cohen and Harcourt provide the reader with context and guidance for making sense of this central, contentious and often difficult literature.
Selection of articles from various sources.
Includes bibliographical references and indexes.
osc 22/01/14
Loan
Keywords: Capital; Economics; Capital theory